2003
DOI: 10.1023/b:brea.0000003969.21267.81
|View full text |Cite
|
Sign up to set email alerts
|

Potent Killing of Paclitaxel- and Doxorubicin-resistant Breast Cancer Cells by Calphostin C Accompanied by Cytoplasmic Vacuolization

Abstract: Drug resistance is a major impediment to the successful treatment of breast cancer using chemotherapy. The photoactivatable drug calphostin C has shown promise in killing select drug-resistant tumor cells lines in vitro. To assess the effectiveness of this agent in killing doxorubicin- or paclitaxel-resistant breast tumor cells and to explore its mode of action, MCF-7 cells were exposed to increasing concentrations of either doxorubicin or paclitaxel until maximum resistance was obtained. This resulted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…On the contrary, no evidence of either feature has been detected in the A 0 -treated cells, thus excluding that the copper complex triggers an apoptotic pathway. Indeed, while selected examples of caspase-independent or nuclear fragmentation-independent apoptotic deaths have been described (see for review, respectively, Kolenko et al 2000;and Ferri and Kroemer 2000), the simultaneous absence of both features is considered a hallmark of nonapoptotic cell death (Szende et al 1995;Sasaki et al 2003;Guo et al 2003;Wojcik et al 2004;Kelly et al 2004;Wang et al 2004;Hirai and Harada 2004;Naumann et al 2004). The results presented also demonstrate that A 0 inhibits the activation of caspase-3 caused by cisplatin.…”
Section: Discussionsupporting
confidence: 50%
“…On the contrary, no evidence of either feature has been detected in the A 0 -treated cells, thus excluding that the copper complex triggers an apoptotic pathway. Indeed, while selected examples of caspase-independent or nuclear fragmentation-independent apoptotic deaths have been described (see for review, respectively, Kolenko et al 2000;and Ferri and Kroemer 2000), the simultaneous absence of both features is considered a hallmark of nonapoptotic cell death (Szende et al 1995;Sasaki et al 2003;Guo et al 2003;Wojcik et al 2004;Kelly et al 2004;Wang et al 2004;Hirai and Harada 2004;Naumann et al 2004). The results presented also demonstrate that A 0 inhibits the activation of caspase-3 caused by cisplatin.…”
Section: Discussionsupporting
confidence: 50%
“…When the PKC inhibitor calphostin C (100 nmol/L) was applied, TRPV6 activity was diminished. Furthermore, tamoxifen had no inhibitory effect in the presence of calphostin C. It was shown previously that calphostin C can reduce MCF-7 cell viability very potently (43). However, because TRPV6-mediated barium entry was also inhibited by tamoxifen, and because barium does not bind to calmodulin (44), we conclude that tamoxifen does not inhibit TRPV6 function through augmentation of calmodulin-mediated inactivation.…”
Section: Discussionmentioning
confidence: 47%
“…Compartments on autophagy to lysosome pathway are vacuolated upon exposure to various substances including chloroquine (Fedorko et al 1968). Endoplasmic reticulum is vacuolated by a panel of substances such as taxol (Chen et al 2008), calphostin C (Guo et al 2003), and 15-deoxy-Δ 12,14 -prostaglandin J 2 (Kar et al 2009) been shown that organic cation transporter (OCT), a member of the SLC family, plays major role in the delivery of organic amines into cells (Koepsell et al 2007). Carrier-mediated processes would be expected to play important roles in the transport of organic amines into the cells when these agents are added at concentrations around and below the K m value of the carrier systems.…”
Section: Transport Into Cellsmentioning
confidence: 99%
“…Taxol, an anticancer drug, also has been shown to cause ER-derived vacuolization when added at relatively high concentrations (e.g., 70 μM) compared with the dose used to induce mitotic arrest (less than 100 nM) (Chen et al 2008). Interestingly, calphostin C, a well-known inhibitor for protein kinase C, induces ER-derived vacuolation and subsequent death of the cells that are resistant to pacilitaxel (taxol) (Guo et al 2003;Kaul and Maltese 2009), indicating its possible usefulness for cancer therapy. Cytoplasmic vacuolization derived from enlarged/dilated ER upon exposure to these drugs could be rationally interpreted as a consequence of excessive ER stress.…”
Section: Endoplasmic Reticulummentioning
confidence: 99%